Kebijakan Vaksinasi Terhadap Warga Negara Indonesia Di Era Pandemi Covid-19 - Rudi Erwin Kurniawan; Ardiansah Ardiansah; Sudi Fahmi (Faculty of Law, Diponegoro University, 2022)
This article aims to examine the vaccination policy for Indonesian citizens during the COVID-19 pandemic and to know the Ideal Concept of Implementing COVID-19 Vaccination Against Citizens in Indonesia This study uses a normative research method in juridical research. Based on the research results, it is known that the COVID-19 pandemic has made the government set an emergency status in Indonesia through Presidential Decree No. 11 of 2020. One of the efforts to overcome the pandemic is vaccination efforts. However, in the community, there are pros and cons related to the vaccination. Some communities refuse to be vaccinated. Therefore, Vaccination in the context of handling COVID-19 is a right as well as an obligation of citizens, meaning that there is a person's right to choose health services for him. However, it can be seen in the context of the COVID-19 Pandemic that someone who is not vaccinated can actually potentially become a virus carrier for others, so that right can be reduced in order to achieve the state's goal of protecting the entire Indonesian nation and all of Indonesia's bloodshed, which also includes protecting a person's own human rights in order to obtain the right to live a healthy life.Keywords: Vaccination; COVID-19; Citizen AbstrakArtikel ini bertujuan untuk mengkaji kebijakan vaksinasi terhadap warga negara Indonesia di masa pandemic COVID-19 dan mengetahui konsep Ideal Pemberlakuan Vaksinasi COVID-19 Terhadap Warga Negara di Indonesia. Penelitian ini menggunakan metode penelitian yuridis normatif. Berdasarkan hasil penelitian diketahui bahwa Pandemi COVID-19 membuat pemerintah menetapkan status kedaruratan di Indonesia, melalui keputusan Presiden Nomor 11 Tahun 2020. Salah satu upaya dalam rangka mengatasi pandemi adalah upaya vaksinasi. Namun, di masyarakat timbul pro kontra terkait vaksinasi tersebut. Beberapa kalangan masyarakat menolak untuk divaksin. Oleh sebab itu. Vaksinasi dalam rangka penanganan COVID-19 adalah suatu hak sekaligus kewajiban dari warga negara artinya terdapat hak seseorang untuk memilih pelayanan kesehatan baginya. Namun, bisa dilihat pada konteks Pandemi COVID-19, seseorang yang tidak divaksin justru dapat berpotensi menjadi virus carrier bagi orang lain, maka hak tersebut dapat dikurangi dalam rangka untuk mencapai tujuan negara yakni melindungi segenap bangsa Indonesia dan seluruh tumpah darah Indonesia dan juga termasuk melindungi hak asasi seseorang itu sendiri dalam rangka memperoleh hak untuk hidup secara sehat.Kata Kunci : Vaksinasi; COVID-19; Warga negara